2019
DOI: 10.1093/mnras/stz3105
|View full text |Cite
|
Sign up to set email alerts
|

The GALAH Survey: Chemically tagging the Fimbulthul stream to the globular cluster ω Centauri

Abstract: Using kinematics from Gaia and the large elemental abundance space of the second data release of the GALAH survey, we identify two new members of the Fimbulthul stellar stream, and chemically tag them to massive, multi-metallic globular cluster ω Centauri. Recent analysis of the second data release of Gaia had revealed the Fimbulthul stellar stream in the halo of the Milky Way. It had been proposed that the stream is associated with the ω Cen, but this proposition relied exclusively upon the kinematics and met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 97 publications
1
16
0
Order By: Relevance
“…Dating back to Lloyd Evans (1983), a bimodal behavior has now been established; for instance, from their highresolution analysis of 113 RR Lyr stars in ωCen Magurno et al (2019) reported solar [Y/Fe] values for stars more metal poor than approximately −1.5 dex, while the more metal-rich component showed enhanced element abundances. This is also seen in terms of a significantly larger scatter above that metallicity cut in the data of Simpson et al (2020), among others. Furthermore, the values for [La/Fe] found by Johnson & Pilachowski (2010) also show a clear bimodality.…”
Section: Fe-peak Elementssupporting
confidence: 51%
See 3 more Smart Citations
“…Dating back to Lloyd Evans (1983), a bimodal behavior has now been established; for instance, from their highresolution analysis of 113 RR Lyr stars in ωCen Magurno et al (2019) reported solar [Y/Fe] values for stars more metal poor than approximately −1.5 dex, while the more metal-rich component showed enhanced element abundances. This is also seen in terms of a significantly larger scatter above that metallicity cut in the data of Simpson et al (2020), among others. Furthermore, the values for [La/Fe] found by Johnson & Pilachowski (2010) also show a clear bimodality.…”
Section: Fe-peak Elementssupporting
confidence: 51%
“…Similarly, genuine GCs are infamous for having a pronounced Na-O anticorrelation, which is also prominently seen in ωCen (Norris & Da Costa 1995b;Gratton et al 2011;Simpson et al 2020) and particularly extended below −1.3 dex (Marino et al 2011). In Fig.…”
Section: Light Elements: C N O Namentioning
confidence: 69%
See 2 more Smart Citations
“…The search for field stars that were born in GCs (Lind et al 2015;Martell et al 2016;Fernández-Trincado et al 2015b, 2016a,b,c,d, 2020aSimpson et al 2020) is one clear example of the power of chemical tagging. This is possible because GCs appear to be the only environment responsible for the presence of light-element anti-correlations at all stellar evolutionary phases (e.g., Martell et al 2016;Pancino et al 2017;Bastian & Lardo 2018;Masseron et al 2019;Mészáros et al 2020), unless they are part of a binary system (Bastian & Lardo 2018;Fernández-Trincado et al 2019a), or part of the new kind of recently discovered anomalous Phosphorus-rich field stars (see, e.g., Masseron et al 2020).…”
Section: Introductionmentioning
confidence: 99%